2023
DOI: 10.1002/cam4.6645
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world outcomes of 18,186 metastatic solid tumor outpatients: Baseline blood cell counts correlate with survival after immune checkpoint inhibitor therapy

Jerome H. Goldschmidt,
Lin‐Na Chou,
Philip K. Chan
et al.

Abstract: BackgroundPatient survival in advanced/metastatic melanoma, non‐small cell lung cancer (NSCLC), and renal cell carcinoma (RCC) has improved with immune checkpoint inhibitors (ICI). Biomarkers' role in prognosis and treatment has been limited by conflicting trial results.MethodsThis retrospective, observational study analyzed baseline demographic, clinical, laboratory, and treatment data versus outcomes of The US Oncology Network adult outpatients. Patients with advanced/metastatic melanoma, NSCLC, or RCC treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Several studies have shown an improved prognosis with TATE or evidence of eosinophil degranulation in various types of solid tumors ( 35 , 45 47 ). In a large national cohort of metastatic solid tumor could show better OS correlated with increased eosinophil count ( 16 ). Moreira et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown an improved prognosis with TATE or evidence of eosinophil degranulation in various types of solid tumors ( 35 , 45 47 ). In a large national cohort of metastatic solid tumor could show better OS correlated with increased eosinophil count ( 16 ). Moreira et al.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter, retrospective study analyzed the correlation between baseline patient characteristics and OS in 18,186 patients treated with ICIs alone or combined with chemotherapy or target therapy, including 12,416 patients with NSLCL [54]. OS was signifi-cantly longer in patients with high levels of basal albuminemia and elevated eosinophil and lymphocyte counts (p < 0.0001).…”
Section: Possible Predictors Of Response To Immunotherapy Rechallengementioning
confidence: 99%